Palliative care development in the Asia-Pacific region: an international survey from the Asia Pacific Hospice Palliative Care Network (APHN). Issue 1 (10th July 2014) - Yamaguchi, Takashi; Kuriya, Meiko; Morita, Tatsuya; Agar, Meera; Choi, Youn Seon; Goh, Cynthia; Lingegowda, K B; Lim, Richard; Liu, Rico K Y; MacLeod, Roderick; Ocampo, Rhodora; Cheng, Shao-Yi; et al.
Abstract : Background: Although palliative care is an important public healthcare issue worldwide, the current situation in the Asia-Pacific region has not been systematically evaluated. Objectives: This survey aimed to clarify the current status of palliative care in the Asia-Pacific region. Methods: Questionnaires were sent to a representative physician of each member country/region of the Asia Pacific Hospice Palliative Care Network (APHN). The questionnaire examined palliative care service provision, information regarding physician certification in palliative care, the availability of essential drugs for palliative care listed by the International Association for Hospice and Palliative Care (IAHPC) and the regulation of opioid-prescribing practice. Results: Of the 14 member countries/regions of the APHN, 12 (86%) responded. Some form of specialist palliative care services had developed in all the responding countries/regions. Eight member countries/regions had physician certifications for palliative care. Most essential drugs for palliative care listed by the IAHPC were available, whereas hydromorphone, oxycodone and transmucosal fentanyl were unavailable in most countries/regions. Six member countries/regions required permission to prescribe and receive opioids. Conclusions: The development of palliative care is in different stages across the surveyed countries/regions in the Asia-Pacific region. Data from this survey can be used as baseline data for monitoring the development of palliative care in this region.